Pengaruh Kualitas Pelayanan, Promosi, Dan Lokasi Terhadap Keputusan Konsumen Menggunakan Apartemen Via Alma Di Cikarang - Seni Aprilia (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
The growth of hotels and apartments in Indonesia is increasing every year, this is driven by the increasing number of tourist visits in Indonesia. As a result, competition in the hotel sector is currently getting tighter, especially to get customers so that they can meet the target Occupancy Rate and business profit. This study aims to determine the effect of Service Quality, Promotion, and Location on the Decision to Use Via Alma Apartments in Cikarang. Via Alma Apartments was established in December 2018, with 148 rooms, equipped with a swimming pool, tennis court, futsal field, and other facilities. The research method is associative, data collection techniques using surveys, and data analysis using Multiple Regression, F Test and t Test. The population of the study were 270 consumers staying at Via Alma Apartments Cikarang and a sample of 90 respondents. The results of the study showed that Service Quality, Promotion, and Location simultaneously influenced Consumer Decisions to use apartment services. Partially, Service Quality and Location had a positive and significant effect on Consumer Decisions to use apartment services, while Promotion had a positive but not significant effect on Consumer Decisions to use apartment services. Apartment management should increase promotions, so that consumers become more interested in using Via Alma apartment services.